Does The Validity of a Sale and Purchase Deed Persist When Underlying Debt Is Concealed? - Pranata, Kimas; Samosir, Tetti; Sihombing, B. F. (Jurnal Ilmu Hukum Kyadiren, 2025)
This study is motivated by the widespread practice of transferring land rights through deeds of sale and purchase that, in substance, are essentially based on debt obligations. The research aims to analyze the nature and characteristics of unlawful acts (PMH) as defined in Article 1365 of the Civil Code, examine the validity of simulative land sale and purchase deeds, and assess the legal responsibility of the Land Deed Officials (PPAT) in transactions that do not reflect the true intent of the parties involved. Employing a normative legal methodology with statutory, jurisprudential, and doctrinal approaches, the study finds that the elements of unlawful acts are met, and while the deeds of sale and purchase are formally valid, they are materially defective. Furthermore, PPATs have been found negligent in fulfilling their duty to verify the parties’ genuine intentions. The study concludes that regulatory reforms and heightened diligence by PPATs are essential to ensure substantive justice in land transactions.